Persepsi Mahasiswa Pada Digitalisasi Pajak Dan Kemauan Membayar Pajak - Situmorang, Boby; Ismail, Marthinus (STAI Denpasar Bali, 2024)
The purpose of this study was to determine students' perceptions on tax digitalization in increasing willingness to pay taxes. This quantitative research method discussed the general description of student perceptions of tax digitization, willingness to pay taxes and conducts regression analysis and significance tests. Data collection using questionnaires with a sample of 90 people. The results of research based on student perceptions show that tax digitalization had a significant effect on the willingness to pay taxes.